JUMPA Vol.3 No.2 Juni 2016 PENERAPAN STRATEGI BALANCE SCORE CARD DAN SUMBER DAYA STRATEGIS TERHADAP KINERJA PERUSAHAAN: PENERAPAN STRATEGI BALANCE SCORE CARD DAN SUMBER DAYA STRATEGIS TERHADAP KINERJA PERUSAHAAN - Setyani Dwi Lestari Universitas Budi Luhur (Jurnal Manajemen dan Perbankan (JUMPA), 2016)
This study aims to explain how to manage Strategic Human Resource Management with ScoreCard Maps that Scorecard has affect to highly performance. Competing for the future with Balance Scorecard would be revolutionaries the tools and concepts. Those concepts provide the wealth of the experience on this work is based and it also explores new ways to measure organizational performance.